2019
DOI: 10.1101/637462
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adult neurogenesis promotes efficient, nonspecific search strategies in a spatial alternation water maze task

Abstract: Goal-directed navigation requires learning strategies that are efficient and minimize costs. In some cases it may be desirable to flexibly adjust behavioral responses depending on the cues that vary from one episode to the next. In others, successful navigation might be achieved with inflexible, habit-like responses that reduce cognitive load. Adult neurogenesis is believed to contribute to the spatial processing functions of the hippocampus, particularly when behavioral flexibility is required. However, littl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Temperature-dependent spatial functions of newborn neurons. While some have reported acquisition and short term reference memory deficits in the spatial water maze in neurogenesis-deficient animals (14,69,72), a majority of studies have found intact spatial learning (2,6,7,15,(17)(18)(19)(20)(21)(22), raising questions about the necessity of adult neurogenesis for spatial learning. Our findings indicate that the degree of stress and/or aversiveness present at the time of learning is critical (as suggested by ( 73)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature-dependent spatial functions of newborn neurons. While some have reported acquisition and short term reference memory deficits in the spatial water maze in neurogenesis-deficient animals (14,69,72), a majority of studies have found intact spatial learning (2,6,7,15,(17)(18)(19)(20)(21)(22), raising questions about the necessity of adult neurogenesis for spatial learning. Our findings indicate that the degree of stress and/or aversiveness present at the time of learning is critical (as suggested by ( 73)).…”
Section: Discussionmentioning
confidence: 99%
“…Adult hippocampal neurogenesis has been implicated in many of the mnemonic functions of the hippocampus, including memory for temporal events (1-3), locations (4), contexts (5,6), objects (7,8) and conspecifics (9), as well as the consolidation (10,11) and forgetting (12) of memory. While spatial memory functions may be particularly apparent in conditions that maximize conflict or interference, such as when a goal changes location (13)(14)(15)(16), it is notable that many of studies have failed to find a role for new neurons in learning and short-term reference memory in the spatial water maze, a task that is highly sensitive to hippocampal disruption (2,6,7,(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with former studies, we found that Cyclin D2 −/− mice were not generally impaired in learning the spatial memory task, but rarely used the most efficient hippocampus-dependent search strategies and showed a lower route efficiency on day 2 and 3-after the first post-learning sleep. Route efficiency and search strategy depend on the use of a cognitive map encoded in the hippocampal formation 46,47 . The use of the most sophisticated search strategies has been shown to be a reliable qualitative parameter for hippocampus-dependent learning 39,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Route efficiency and search strategy depend on the use of a cognitive map encoded in the hippocampal formation 46,47 . The use of the most sophisticated search strategies has been shown to be a reliable qualitative parameter for hippocampus-dependent learning 39,47 . Accordingly, age-dependent decline of adult neurogenesis is associated with less frequent use of hippocampal search strategies 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Together these findings suggest a possible relationship between the level of postnatal neurogenesis and overall spatial performance. Postnatal hippocampal neurogenesis has been shown to have little role in short term spatial memory in the water maze (Snyder et al 2005), however it does impact spatial search strategies (Yu et al 2019). The spatial impairment in the cKO mice could also be due to more direct effects of aberrant cholinergic signaling on encoding, retrieval and task performance.…”
Section: Discussionmentioning
confidence: 99%